EFEKTIVITAS MEDIA SOSIAL SEBAGAI MEDIA PROMOSI - Arum Wahyuni Purbohastuti (Tirtayasa Ekonomika, 2017)
This study aims to find out how effective social media is used as a means to promote products among students.The method used in this study is a qualitative method that is descriptive research and tends to use analysis. There were eight students who were made as respondents.Based on the research that has been done, social media is very effective as a promotion media because of the eight students making social media the most frequently used promotional media